Molecular markers in cell cycle visualisation during development and stress conditions in Arabidopsis thaliana - Olivia S. Hazelwood; M. Arif Ashraf (Quantitative Plant Biology)
Plant growth and development are tightly regulated by cell division, elongation, and differentiation. A visible plant phenotype at the tissue or organ level is coordinated at the cellular level. Among these cellular regulations (cell division, elongation and differentiation), cell division in plants follows the same universal mechanisms across kingdoms of life, and involves conserved cell cycle regulatory proteins (cyclins, cyclin-dependent kinase and cell cycle inhibitors). Cell division is regulated through distinct cell cycle steps (G1, S, G2 and M), and these individual steps are visualised using transgenic marker lines. As a result, a quantitative cell cycle approach in plants during development and stress conditions relies on the accuracy of cell cycle markers. In this perspective article, we highlight the available cell cycle marker lines in plants, common practices within plant biology communities based on existing literature and provide a road map to a thorough quantitative approach of cell cycle regulation in plants.